Spontaneously Hypertensive Rat Chromosome 2 with Mutant Connexin 50 Triggers Divergent Effects on Metabolic Syndrome Components - Šeda, O; Křenová, D; Šedová, L; Kazdová, L; Krupková, M; Chylíková, B; Liška, F; Křen, V (Folia biologica, 2017)
Metabolic syndrome is a frequent condition with multifactorial aetiology. Previous studies indicated the presence of genetic determinants of metabolic syndrome components on rat chromosome 2 (RNO2) and syntenic regions of the human genome. Our aim was to further explore these findings using novel rat models. We derived the BN-Dca and BN-Lx.Dca congenic strains by introgression of a limited RNO2 region from a spontaneously hypertensive rat strain carrying a mutation in the Gja8 gene (SHR-Dca, dominant cataract) into the genomic background of Brown Norway strain and congenic strain BN-Lx, respectively. We compared morphometric, metabolic and cytokine profiles of adult male BN-Lx, BN-Dca and BN-Lx.Dca rats. We performed in silico comparison of the DNA sequences throughout RNO2 differential segments captured in the new congenic strains. Both BN-Dca and BN-Lx.Dca showed lower total triacylglycerols and cholesterol concentrations compared to BN-Lx. Fasting insulin in BN-Dca was higher than in BN-Lx.Dca and BN-Lx. Concentrations of several proinflammatory cytokines were elevated in the BN-Dca strain, including IL-1α, IL-1β, IFN-γ and MCP-1. In silico analyses revealed over 740 DNA variants between BN-Lx and SHR genomes within the differential segment of the congenic strains. We derived new congenic models that prove that a limited genomic region of SHR-Dca RNO2 significantly affects lipid levels and insulin sensitivity in a divergent fashion.
Keywords: mutace; Animals; cholesterol; hypertenze; Interferon-gamma; Interleukin-1alpha; triglyceridy; Metabolic Syndrome; Triglycerides; Mutation; metabolický syndrom; interferon gama; Cholesterol; Chromosomes, Mammalian; chemokin CCL2; Hypertension; Interleukin-1beta; Male; interleukin-1alfa; Chemokine CCL2; krysa rodu Rattus; interleukin-1beta; konexiny; zvířata; mužské pohlaví; savčí chromozomy; Rats; Connexins